Pengaruh Online Customer Review dan Online Customer Rating terhadap Purchase Decision di Tiktok Shop: Studi Kasus Pada Generasi Z di Bandar Lampung - Yeni Arinda; Iskandar Ali Alam; Nuris Sanida (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This investigate was conducted with the point of finding out the impact of Online Client Survey (X1) and Online Client Rating (X2) on Buy Choice (Y) at Tiktok Shop on gen z in Bandar Lampung. In analyzing applying a Quantitative approach. Changes in customer behavior shopping online nowadays are the reason for the ought to get it how audits and appraisals influence online buys as a implies of shopper data. This inquire about included all Tiktok Shop clients in Bandar Lampung by drawing 100 respondents as a test, chosen utilizing purposive testing. The information was analyzed utilizing SPSS with Numerous Straight Relapse examination. The survey was utilized as a information collection instrument. The inquire about discoveries appear that the factors Online Client Survey (X1), Online Client Rating (X2) at the same time have a noteworthy impact on Purchase Decision (Y) at Tiktok Shop. Buy Choice (Y) isn't altogether impacted by Online Client Survey. Online Client Rating includes a mostly critical impact on Buy Choice (Y) at Tiktok Shop.